Kurt Eisner : a modern life - Gurganus, Albert E. (Camden House, 2018)
The first comprehensive biography in English of the leader of the Bavarian Revolution and Republic of 1918/19, the first Jewish head of a European state and a man who embraced and embodied modernity.
Keywords: Eisner, Kurt, -- 1867-1919.; Eisner, Kurt, -- 1867-1919; Socialists -- Germany -- Biography.; Bavaria (Germany) -- History -- Revolution, 1918-1919.; Germany -- History -- Revolution, 1918.; Socialistes -- Allemagne -- Biographies.; Bavière (Allemagne) -- Histoire -- 1918-1919 (Révolution); Allemagne -- Histoire -- 1918 (Révolution); HISTORY -- Europe -- Germany.; Socialists; Germany; Germany -- Bavaria; 1918-1919; Bavarian republic.; German Jews.; Kurt Eisner.; Munich revolution.; political activism.; pre-Nazi period.; rise of fascism.; Biography; Biographies; History; Biographies.